Frontispiece: Total Synthesis of Anti‐MRSA Active Diorcinols and Analogues. Issue 44 (7th August 2020) - Boehlich, G. Jacob; de Vries, Jessica; Geismar, Olivia; Gudzuhn, Mirja; Streit, Wolfgang R.; Wicha, Sebastian G.; Schützenmeister, Nina
Abstract : Seven diorcinols and related structures (diaryl ethers) were synthesized with a short and divergent approach. The key step was identified to be the Pd‐catalyzed diaryl ether coupling. Three of the synthesized members this natural product class exhibit anti‐MRSA and biofilm activity. For more information, see the Communication by Schützenmeister et al. on page 9846 ff.